ANALYSIS OF NURSING CARE IN NSTEMI PATIENTS WITH THE APPLICATION OF DEEP BREATHING RELAXATION AND MURATTAL THERAPY TO OVERCOME THE PROBLEM OF ACUTE PAIN - Milaningrum, Kartika; Ainiyah, Nur; Soleha, Umdatus; Firdaus (Nurse and Holistic Care, 2024)
Introduction: Non-ST Elevation Myocardial Infarction is usually caused by severe narrowing of the coronary arteries, this can cause chest pain that can last long and intense, cold sweat, nausea and vomiting, and feeling as if you are facing death. Objective: This study investigates the application of deep breathing relaxation and Murattal therapy in nursing care for NSTEMI patients experiencing acute pain. The research assesses their effectiveness in pain management, revealing significant reductions in pain levels post-intervention. These results suggest their potential integration into nursing practice and the need for further exploration into non-pharmacological pain management strategies. Methods: This research uses a case study design with a nursing care process approach. The participant was a 55-year-old patient with a diagnosis of NSTEMI who experienced acute pain. The instrument used is an observation sheet with a measurement scale using a Numerical Rating Scale. Results: Before deep breathing relaxation therapy and Murattal therapy, it was found that the patient experienced moderate pain with complaints of pain during strenuous activity, pain like stabbing, pain in the chest that penetrated the back, pain scale 5 (moderate pain), persistent pain frequency, whereas, after management pain relief, deep breathing relaxation therapy, Al-Qur'an Murattal therapy 1x/day for a total of 3 days with a total duration± 25 minutes, it was found that the patient's pain decreased to become lighter with complaints of pain during strenuous activities, the quality of pain was like stabbing, pain in the chest penetrated to the back, pain scale 2 (mild pain), the frequency of pain began to disappear. Conclusions: The conclusion from the results of the case study shows that deep breathing relaxation therapy and Murattal therapy which are carried out routinely and according to the procedure are effective for reducing chest pain in Mr.I with NSTEMI. Suggestions for nurses to routinely provide deep breathing relaxation therapy and Murattal therapy to patients who experience NSTEMI.